2020
DOI: 10.1109/jsen.2020.2998827
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Comparison for Corona Discharge Detection Under Low Pressure Conditions

Abstract: Low pressure environments, situate insulation systems in a challenging position since partial discharges (PDs), corona and arc tracking are more likely to develop. Therefore, specific solutions are required to detect such harmful phenomena before major failure occurrence. This paper deals with three low-cost and small-size sensing methods, i.e., a single loop antenna, a visible-UV imaging sensor and the measurement of the leakage current to detect corona in the early stage, thus anticipating the appearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…The results presented in Figure 4 clearly show that CEV values are mainly affected by ambient pressure. The results plotted in Figure 4 are in accordance with previous studies analyzing gas discharges for specific supply frequencies [ 7 ]. This effect is due to the fact that the mean free path between ion collisions is inversely proportional to air density, and thus, a larger number of successful secondary ionizations are produced at a lower pressure, so that partial discharges can occur at lower voltages than the ones required at atmospheric pressure [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results presented in Figure 4 clearly show that CEV values are mainly affected by ambient pressure. The results plotted in Figure 4 are in accordance with previous studies analyzing gas discharges for specific supply frequencies [ 7 ]. This effect is due to the fact that the mean free path between ion collisions is inversely proportional to air density, and thus, a larger number of successful secondary ionizations are produced at a lower pressure, so that partial discharges can occur at lower voltages than the ones required at atmospheric pressure [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…The sensibility to detect corona discharges of the image sensor has been tested and compared with that of the leakage current sensor, obtaining very close results, as shown in Figure 4 and in Table 4 , where the percentage differences are calculated, which are very low. A similar comparison was performed in [ 7 ] where it was also concluded that the imaging method with a CMOS camera has almost the same sensitivity as other sensitive methods for corona detection.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, operation at high-voltage pose aircraft insulation systems in a big challenge, since the combined effect of higher voltages, high compactness ratios, high power-to-weight ratios, higher operating frequencies and low-pressure operation greatly increase the risk of partial discharge (PD) occurrence [1,2]. It is well known that low-pressure operation significantly reduces the dielectric strength of air [3][4][5], and thus, surface discharges tend to initiate at lower voltages compared to the voltages at which they initiate at sea-level. The reduction of the dielectric strength of atmospheric air at low pressure presents several disadvantages related to premature insulation degradation, insulation lifetime reduction and finally complete electrical breakdown [6] with the consequent risk of fire [7,8] and disconnection of circuits, which can lead to emergency landings, aborted operations or severe accidents [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there has been more focus on non-contact methods of monitoring insulator surfaces for convenience and reliability. Such methods include acoustic, thermal [ 2 , 5 , 6 ], UV intensity, infrared [ 7 , 8 ], etc.…”
Section: Introductionmentioning
confidence: 99%